Indonesian Coastal Management and Corporate Social Responsibility - Muhammad, Nur Alifhia; Haning, Moch Thahir; Yunus, Muhammad (Institute Of computer Science (IOCS), 2025)
This study examines the effectiveness of PT Huadi Nickel Alloy Indonesia's Corporate Social Responsibility (CSR) program in the coastal area of Bantaeng Regency, South Sulawesi, Indonesia, focusing on its impact on the local community, particularly in addressing clean water scarcity due to industrial activities. A qualitative approach with a descriptive method was employed, using interviews, observations, and document analysis to collect data from key informants. The effectiveness was analyzed using three indicators: goal attainment, integration, and adaptation. The results show that the CSR program has provided positive impacts but has not been entirely comprehensive due to budget limitations and conflicts among community members. The integration of the program has been facilitated through communication and coordination between stakeholders, but further efforts are needed to enhance integration and align the program with the community's needs. The adaptation has been supported by local government regulations, but strengthening collaboration is necessary to ensure sustainability. In conclusion, despite limitations and challenges, the CSR program has provided positive impacts for the coastal community. Further efforts are required to increase coverage, expand beneficiaries, and strengthen collaboration to ensure the program's sustainability and effectiveness in improving the welfare of the coastal community